Inhibition of catechol-O-methyltransferase activity in human breast cancer cells enhances the biological effect of the green tea polyphenol (-)-EGCG - LANDIS-PIWOWAR, KRISTIN (2010)
Tea is one of the most popular beverages in the world and has been studied extensively as a health-promoting beverage that may act to prevent a number of chronic diseases and cancers. (-)-Epigallocatechin gallate [(-)-EGCG], a major component in green tea, is unstable under physiological conditions and methylation of (-)-EGCG by catechol-O-methyltransferase (COMT) is a modification that reduces the biological activity of (-)-EGCG. In the current study, we hypothesized that suppression of COMT activity in human breast cancer cells could increase the proteasome-inhibitory potency of (-)-EGCG and therefore enhance its tumor cell growth-inhibitory activity. We first determined the COMT genotype and basal levels of COMT activity in various human breast cancer cell lines. Furthermore, when breast cancer MDA-MB-231 cells containing high COMT activity were tested, the diminished COMT activity apparently increased the effectiveness of (-)-EGCG via augmented proteasome inhibition and apoptosis induction. This study supplements the previous findings that methylated (-)-EGCG is less bioactive and supports the notion that COMT inhibition may increase the anti-cancer properties of tea polyphenols and the combination may serve as a novel approach or supplemental treatment for breast cancer chemotherapy.